2017
DOI: 10.3389/fnmol.2017.00351
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal and Peripheral Expressed Membrane-Bound UNC93A Respond to Nutrient Availability in Mice

Abstract: Many transporters such as the solute carriers belonging to the Major facilitator superfamily Pfam clan are orphans in that their tissue and cellular localization as well as substrate profile and function are still unknown. Here we have characterized the putative solute carrier UNC93A. We aimed to investigate the expression profile on both protein and mRNA level of UNC93A in mouse since it has not been clarified. UNC93A staining was found in cortex, hippocampus and cerebellum. It was found to be expressed in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 86 publications
7
31
0
Order By: Relevance
“…Additionally, we found that MFSD-6, a member of the Major Facilitator Superfamily Domain (MFSD) family, promotes PLM regrowth ( Figure 1—figure supplement 2F ). MFSD family proteins have 10–12 transmembrane regions ( Yan, 2015 ); some mediate nutrient transport across the blood-brain barrier ( Ceder et al, 2017 ; Perland et al, 2017 ), but most are of unknown function. C. elegans MFSD-6 was previously identified as a regulator of motor circuit activity and mfsd-6(0) mutants are resistant to inhibitors of cholinesterase ( McCulloch et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we found that MFSD-6, a member of the Major Facilitator Superfamily Domain (MFSD) family, promotes PLM regrowth ( Figure 1—figure supplement 2F ). MFSD family proteins have 10–12 transmembrane regions ( Yan, 2015 ); some mediate nutrient transport across the blood-brain barrier ( Ceder et al, 2017 ; Perland et al, 2017 ), but most are of unknown function. C. elegans MFSD-6 was previously identified as a regulator of motor circuit activity and mfsd-6(0) mutants are resistant to inhibitors of cholinesterase ( McCulloch et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ortholog found in C. elegan s is suggested to be a regulatory protein of a potassium channel ( de la Cruz et al, 2003 ). Interestingly, there is also evidence that UNC93A is a membrane-bound protein ( Levin and Horvitz, 1992 ; Liu et al, 2002 ; Ceder et al, 2017 ) with a 2D topology resembling an authentic transporter according to predictions ( Ceder et al, 2017 ; Perland et al, 2017a ). In D. melanogaster , the ortholog CG4928 was found to be highly expressed in the Malpighian tubules, equivalent to the human kidneys ( Wang et al, 2004 ), to be important for hemocyte development ( Stofanko et al, 2008 ), and to be one of several genes that confer manganese toxicity resistance ( Mohr et al, 2018 ).…”
Section: Introductionmentioning
confidence: 98%
“…Members of the MFS are facilitators and secondary active transporters with various expressions, functions, and substrate profiles ( Pao et al, 1998 ; Reddy et al, 2012 ). Like many SLCs of MFS type, UNC93A is evolutionary conserved ( Ceder et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations